Trade policy and Georgian exports - Volkhart Vincentz (Osteuropa-Institut Regensburg, 2008)
As a mall country among Georgia's growth factors in future might well be foreign trade. The close cooperation with the EU within the European neighborhood policy centers on improving and facilitating trade between the partners. In 2006 the EU granted Georgia the GSP+ status which allows almost duty free imports of Georgian products in the EU. The extension of these trade preferences is negotiated in the realm of a deep and com-prehensive free trade agreement between the EU and Georgia. A closer look on the trade data reveal that no trade enhancing effect of the GSP+ can be detected. The available trade data are significantly blurred by the inclusion of energy trade from Georgia which is likely only transit trade from Azerbaijan and Kazakhstan. If these export items and the movements of some raw material prices are removed from the data no export enhancing effect can be found. In addition, in the past the composi-tion of Georgian exports remained highly biased towards raw materials and simple products. Improvements in export came from the export of services, namely tourism and pipe-line transport service. Later is a significant source of income as well as the transfers of Georgian migrants working abroad? The export of pipeline service might increase in future further if envisaged additional pipelines over Georgian soil realize. Since these are mainly built with foreign capital increasing profit repatriation will result in higher capital outflows in future. At the moment the EU negotiates an deep and comprehensive free trade agreement with Georgia which foresees beyond the abolition of tariffs the removal of all types of non-tariff barriers (NTBs) . An important part of trade facilitation would be the adop-tion of EU standards and norms which hinder at the moments Georgian exporters. Al-though the EU is prepared to contribute with financial and technical help the removal of NTBs is costly for Georgian firms. The available studies forecast however significant positive effects from a comprehensive trade liberalization between the partners. Al-though not captured by the mentioned feasibility studies on a comprehensive EU-Georgian trade agreement, the strongest export enhancing effect for Georgia will only come from broadening the existing export basket. To do so best chances for Georgian firms are seen in transit services and the production of parts and components as a sup-plier for multinational firms. The existing range of export goods does not exploit effec-tively the comparative advantages of the country.
Keywords: 330; Exportinduziertes Wachstum; Außenwirtschaftspolitik; Freihandelszone; Handelsbilanz; Wirkungsanalyse; Georgien